Pengaruh Model Pembelajaran Problem Based Learning Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas IX SMP N 1 Salak Kabupaten Pakpak Bharat Tahun Ajaran 2023/2024 - Juliana Padang; Oktober Tua Aritonang; Pestaria Naibaho (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The aim of this research is to determine the positive and significant influence of the Problem Based Learning Model on the Learning Motivation of Christian Religious Education in Class IX Students of SMP N 1 Salak, Pakpak Bharat Regency, Academic Year 2023-2024. The research method used is a quantitative research method and a pre-experimental design research type in the form of "One Shot Case Study". The population was all class IX students of SMP N 1 Salak, totaling 146 people and a sample of 32 people was determined using the Purposive Sample technique. Data was collected using a positive closed questionnaire with 17 items and 17 items of observation sheet for variable Y. The results of data analysis showed that there was a positive and significant influence of the Problem Based Learning Model on the Motivation to Learn Christian Religious Education in Class IX of SMP N 1 Salak, Pakpak Bharat Regency, Year Teachings 2023-2024: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.547 > rtable(a=0.05,n=32) = 0.349. b) Testing a significant relationship obtained tcount= 3.576 > ttable(a=0.05, dk=n-2=30)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=24.26+0.57X. b) Regression coefficient of determination test (r2) = 29.9%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=14, dk denominator=n-2=32-2=30) namely 12.78 > 2.01. Thus Ha is accepted and H0 is rejected.